The eukaryotic translation initiation factor 3f (eIF3f) interacts physically with the alpha 1B-adrenergic receptor and stimulates adrenoceptor activity. Issue 1 (December 2015) - Gutiérrez-Fernández, Mario; Higareda-Mendoza, Ana; Gómez-Correa, César; Pardo-Galván, Marco
Abstract Background eIF3f is a multifunctional protein capable of interacting with proteins involved in different cellular processes, such as protein synthesis, DNA repair, and viral mRNA edition. In human cells, eIF3f is related to cell cycle and proliferation, and its deregulation compromises cell viability. Results We here report that, in native conditions, eIF3f physically interacts with the alpha 1B-adrenergic receptor, a plasma membrane protein considered as a proto-oncogene, and involved in vasoconstriction and cell proliferation. The complex formed by eIF3f and alpha 1B-ADR was found in human and mouse cell lines. Upon catecholamine stimulation, eIF3f promotes adrenoceptor activityin vitro, independently of the eIF3f proline- and alanine-rich N-terminal region. Conclusions The eIF3f/alpha adrenergic receptor interaction opens new insights regarding adrenoceptor-related transduction pathways and proliferation control in human cells. The eIf3f/alpha 1B-ADR complex is found in mammals and is not tissue specific.